Study of DC partial discharge on dielectric surfaces: Mechanism, patterns and similarities to AC. (March 2021) - Abdul Madhar, Saliha; Rodrigo Mor, Armando; Mraz, Petr; Ross, Rob
Highlights: The Partial Discharges (PD) patterns from surface defects are investigated in this paper. It correlates the dielectric properties of the samples with its PD performance. Studies are conducted on both AC and DC Partial discharges on various test samples. The similarities between AC and DC discharge patterns are presented. The DC patterns for time between discharges ( Δ t i + 1 vs. Δ t i ) resembles a unique fish like pattern. Abstract: This paper presents the investigation on surface discharge behavior of various dielectric samples under DC. It sequentially develops the knowledge base for the study and analysis of the partial discharge (PD) defect with the goal of PD defect identification under DC. In order to facilitate this, the material properties of the dielectric are measured. Finite Element (FEM) simulation is used to obtain the preliminary estimates of the electric field and dielectric properties that concern partial discharge behavior. The DC-PD tests performed on the surface dielectric samples demonstrate a highly plausible behavior based on simulation results and other literature. It also displays a great degree of similarity towards the AC surface discharge behavior. The paper concludes by presenting novel partial discharge fingerprints for the surface PD defect that will aid in defect identification under HVDC.